Task sequencing on oral performance in Portuguese as a foreign language - Sara Santos (Moderna Språk)
This empirical study examined Robinson’s (2010, 2015, 2022) Simplify, Stabilise/ Automatise/ Restructure, Complexify (SSARC) instructional design model of task sequencing. Thirty-four university learners of Portuguese as a foreign language participated in the research. The analysis employed a monologic narrative task and two independent variables: “± here-and-now” and “± planning time”. Measures of syntactic complexity, lexical diversity, accuracy, and fluency were selected to analyse the learners’ output. A between-subjects design was adopted. Participants were divided into two groups: (i) sequencing group, in which the students (n=15) performed three tasks with different levels of cognitive complexity (simple task – complex task – more complex task); (ii) individual performance group (n=19), in which the students performed only one task (simple task, complex task, or more complex task). The inferential statistical tests showed gains in fluency and syntactic complexity (coordination index) regarding the complex task in the sequencing group, and increased accuracy and fluency for the more complex task, as compared to individual group performance. The SSARC model was considered to have pedagogical merit, which can help teachers design task-based syllabuses. To the best of our knowledge, this is the first study to fully test the SSARC model applied to oral task sequencing in Portuguese as a foreign language.